S-ketamine alleviates depression-like behavior and hippocampal neuroplasticity in the offspring of mice that experience prenatal stress - Yan Zhang; Chu-Ke Wei; Ping Wang; Liu-Cheng Zheng; Yang Cheng; Zhen-Hua Ren; Yu-Hong Jin; Yu-You Yao; Huan-Zhong Liu (Scientific Reports)
Abstract Prenatal stress exerts long-term impact on neurodevelopment in the offspring, with consequences such as increasing the offspring’s risk of depression in adolescence and early adulthood. S-ketamine can produce rapid and robust antidepressant effects, but it is not clear yet whether and how S-ketamine alleviates depression in prenatally stressed offspring. The current study incestigated the preliminary anti-depression mechanism of S-ketamine in prenatally stressed offspring, particularly with regard to neuroplasticity. The pregnant females were given chronic unpredictable mild stress on the 7th-20th day of pregnancy and their male offspring were intraperitoneally injected with a single dose of S-ketamine (10 mg/kg) on postnatal day 42. Our findings showed that S-ketamine treatment counteracted the development of depression-like behaviors in prenatally stressed offspring. At the cellular level, S-ketamine markedly enhanced neuroplasticity in the CA1 hippocampus: Golgi-Cox staining showed that S-ketamine alleviated the reduction of neuronal complexity and dendritic spine density; Transmission electron microscopy indicated that S-ketamine reversed synaptic morphology alterations. At the molecular level, by western blot and RT-PCR we detected that S-ketamine significantly upregulated the expression of BDNF and PSD95 and activated AKT and mTOR in the hippocampus. In conclusion, prenatal stress induced by chronic unpredictable mild stress leads to depressive-like behaviors and hippocampal neuroplasticity impairments in male offspring. S-ketamine can produce antidepressant effects by enhancing hippocampal neuroplasticity via the BDNF/AKT/mTOR signaling pathway.